Critical design : a tool to challenge the implicit values behind the Fourth Industrial Revolution / Fernando Carrasco Ferretti and Annie Pedret - Fernando Carrasco, Ferretti; Annie, Pedret (Universiti Teknologi MARA, Perak, 2018)
The Fourth Industrial Revolution is transforming human civilization in its scale, scope and complexity leading to a new landscape of uncertainty never faced before. This paper argues that the practice of Critical Design can help designers to face this uncertainty introducing a new conceptual space of debate. In this new social landscape of uncertainty, new emerging technologies are being implemented without a comprehensive or global view of how these technologies could affect human civilization in the future. Today the practice of design focuses more on exploring and identifying presumably positive applications of these emerging technologies, that it is on identifying and investigating their future adverse consequences. Both the positive and negative impact of these technologies need to be addressed in an integrated way if we are to face the immense challenge of the fourth industrial revolution. This paper addresses the question: What role can the practice of Critical Design play in challenging the values embedded in the technologies of the fourth industrial revolution? The purpose of this paper is to investigate how the practice of Critical Design can be used to create a greater awareness on the impact of decisions designers are taking today. I argue that the practice of Critical Design can be used as a tool to challenge the values embedded in the technologies of the fourth industrial revolution, providing a new conceptual space of debate for designers to test their decisions before they are fully implemented. Depending on how these decisions are addressed, the future of human civilization could be brighter rather than unfortunate.